Increased risk of volume overload with plasma compared with four‐factor prothrombin complex concentrate for urgent vitamin K antagonist reversal - Refaai, Majed A. (Transfusion, 2015)
BACKGROUND: Plasma is commonly used for vitamin K antagonist (VKA) reversal, but observational studies suggest that it is associated with transfusion‐related adverse reactions (e.g., volume overload). However, this issue has not previously been addressed in a randomized controlled trial (RCT). STUDY DESIGN AND METHODS: Factors associated with volume overload were examined using data from two Phase IIIb RCTs comparing plasma with four‐factor prothrombin complex concentrate (4F‐PCC, Beriplex/Kcentra, CSL Behring) for urgent VKA reversal. VKA‐treated patients with major bleeding (NCT00708435) or requiring an urgent surgical or invasive procedure (NCT00803101) were randomly assigned (1:1) to receive either plasma or 4F‐PCC, concomitant with vitamin K. Adverse events (AEs) and serious AEs were prospectively captured up to Day 10 and 45, respectively. Volume overload predictors were evaluated on a univariate and multivariate basis. RESULTS: A total of 388 patients (4F‐PCC, n = 191; plasma, n = 197) were enrolled. Volume overload occurred in 34 (9%) patients (4F‐PCC, n = 9; plasma, n = 25). In univariate analyses, use of plasma (vs. 4F‐PCC), use of nonstudy plasma and/or platelets, race, history of congestive heart failure (CHF), and history of renal disease were associated with volume overload. In multivariate analyses, use of plasma (vs. 4F‐PCC), history of CHF, and history of renal disease were independent volume overload predictors. In an additional analysis restricted to volume overload events recorded up to Day 7, only use of plasma (vs. 4F‐PCC) was an independent volume overload predictor. CONCLUSIONS: After adjusting for other potential risk factors, plasma use was independently associated with a greater risk of volume overload than 4F‐PCC in patients requiring urgent VKA reversal.